Promoting Religious Moderation through Community Engagement: Insights from Religious Counselors in Cinta Damai Village - Mas Ayuna Hasibuan; Samosir, Hasrat Efendi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This study seeks to determine the role of religious counselors in strengthening religious moderation in Cinta Damai Village, Deli Serdang North Sumatra. As part of the da'wah (preaching) movement, religious counselors are in charge of providing religious understanding and resolving community issues. This study uses a qualitative method with a field study approach and descriptive design. This approach allows in-depth data mining related to the views, experiences, and understanding of the community toward the role of religious counselors. Field studies were conducted to obtain contextual and relevant data on the conditions of Cinta Damai Village. The findings reveal that religious counselors have a crucial role in strengthening religious moderation through three main functions: informative, consultative and advocative. Messages about tolerance, interfaith dialog, and legal awareness have proven to be important elements in building a peaceful society. However, religious counselors faced challenges, such as a public misunderstanding of the concept of religious moderation. To address this issue, religious counselors must actively educate people to respect differences and live a harmonious religious life. Eventually, this study confirms that religious counselors play an important role in fostering a peaceful environment.